The Relationship Between Hardiness and Academic Procastination in Final Students Compiling Thesis: Hubungan Antara Hardiness dengan Prokastinasi Akademik pada Mahasiswa Akhir yang Menyusun Skripsi - Navron, Lavida; Dewanti, Ririn (Indonesian Journal of Innovation Studies, 2023)
This study aims to determine the relationship between the 2018 Final Year Students who Compose Thesis at the Psychology Study Program, University of Muhammadiyah Sidoarjo. This research is a type of quantitative research with a correlational approach. The variables in this study are hardiness as the independent variable and academic procrastination as the dependent variable. This research was conducted at Muhammadiyah University of Sidoarjo with a population of 154 students. The sample in this study were 113 students who were taken using simple random sampling technique. Data analysis used the Pearson Product Moment correlation technique with the help of the JASP 0.16 program. The results of data analysis showed that the correlation coefficient was -0.698 with a significance of <0.001, meaning that there was a negative relationship between hardiness and academic procrastination. This means that the higher the hardiness, the lower the academic procrastination, and vice versa, the lower the hardiness, the higher the academic procrastination.